Linezolid and Methicillin-Resistant Coagulase Negative Staphylococci from Anterior nares of Nigerian Tertiary School Students. (Global Journal of Medical Research, 2016)
Abstract not found
Keywords: coagulase-negative staphylococci; antibiotic susceptibility patterns; methicillin-resistant CoNS; linezolid-resistant CoNS; anterior nares; apparently